Bacopa monniera leaf extract ameliorates hypobaric hypoxia induced spatial memory impairment - Sunil Kumar Hota; Kalpana Barhwal; Iswar Baitharu; Dipti Prasad; Shashi Bala Singh; Govindasamy Ilavazhagan (Neurobiology of Disease, 2009)
Hypobaric hypoxia induced memory impairment has been attributed to several factors including increased oxidative stress, depleted mitochondrial bioenergetics, altered neurotransmission and apoptosis. This multifactorial response of the brain to hypobaric hypoxia limits the use of therapeutic agents that target individual pathways for ameliorating hypobaric hypoxia induced memory impairment. The present study aimed at exploring the therapeutic potential of a bacoside rich leaf extract of Bacopa monniera in improving the memory functions in hypobaric conditions. The learning ability was evaluated in male Sprague Dawley rats along with memory retrieval following exposure to hypobaric conditions simulating an altitude of 25,000 ft for different durations. The effect of bacoside administration on apoptosis, cytochrome c oxidase activity, ATP levels, and oxidative stress markers and on plasma corticosterone levels was investigated. Expression of NR1 subunit of N-methyl-d-aspartate receptors, neuronal cell adhesion molecules and was also studied along with CREB phosphorylation to elucidate the molecular mechanisms of bacoside action. Bacoside administration was seen to enhance learning ability in rats along with augmentation in memory retrieval and prevention of dendritic atrophy following hypoxic exposure. In addition, it decreased oxidative stress, plasma corticosterone levels and neuronal degeneration. Bacoside administration also increased cytochrome c oxidase activity along with a concomitant increase in ATP levels. Hence, administration of bacosides could be a useful therapeutic strategy in ameliorating hypobaric hypoxia induced cognitive dysfunctions and other related neurological disorders.